2021
DOI: 10.1210/clinem/dgab353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proton Pump Inhibitors on Glycemic Control and Incident Diabetes: A Systematic Review and Meta-analysis

Abstract: Context Whether proton pump inhibitors (PPI) can improve glycemic control among individuals with diabetes or decrease the risk of incident diabetes in the general population is unclear. Objective To evaluate the impact of PPI therapy on glycemic control among individuals with diabetes and the risk of diabetes among those without diabetes. Results PubMed, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“… 140 Although a comprehensive review of general PPI adverse events is beyond the scope of this article, it is important to note that the Food and Drug Administration (FDA) has specifically cautioned PPI standard dose users on the risks for Clostridioides (formerly clostridium) difficile infection, 141 bone fractures 142 and hypomagnesemia. 143 There have been numerous meta-analyses for standard dose PPI therapy citing both associations and lack of association of PPI use and pneumonia, 144–148 other enteric infections, 149–151 gastric atrophy and cancer, 152–154 chronic kidney disease, 155–159 diabetes, 160 , 161 chronic obstructive lung disease, 162 , 163 dementia, 164–169 cardiovascular disease or cardiovascular events, 170–175 and all-cause mortality. 176–180 However, it is likely that most of the reported potential risks are due to residual confounding within the study design, 180–183 and a large-scale, industry sponsored randomized controlled trial recently emphasized the safety of this medication class and refuted most of the prior proposed associations.…”
Section: Ppi Adverse Events In Adults With Eoementioning
confidence: 99%
“… 140 Although a comprehensive review of general PPI adverse events is beyond the scope of this article, it is important to note that the Food and Drug Administration (FDA) has specifically cautioned PPI standard dose users on the risks for Clostridioides (formerly clostridium) difficile infection, 141 bone fractures 142 and hypomagnesemia. 143 There have been numerous meta-analyses for standard dose PPI therapy citing both associations and lack of association of PPI use and pneumonia, 144–148 other enteric infections, 149–151 gastric atrophy and cancer, 152–154 chronic kidney disease, 155–159 diabetes, 160 , 161 chronic obstructive lung disease, 162 , 163 dementia, 164–169 cardiovascular disease or cardiovascular events, 170–175 and all-cause mortality. 176–180 However, it is likely that most of the reported potential risks are due to residual confounding within the study design, 180–183 and a large-scale, industry sponsored randomized controlled trial recently emphasized the safety of this medication class and refuted most of the prior proposed associations.…”
Section: Ppi Adverse Events In Adults With Eoementioning
confidence: 99%
“…The ability of gastrin to improve glycemic control in T2DM has been indirectly demonstrated by clinical trials that demonstrated improved HbA1C in patients receiving proton pump inhibitors (PPIs), which indirectly elevates serum gastrin levels [ 80 , 81 , 82 ]. Whether this is through improving β-cell function or altering β-cell mass is not known.…”
Section: Current Therapeutic Agentsmentioning
confidence: 99%
“…This is possibly due to the increased gastrin receptor expression, cholecystokinin B receptor (CCKBR), in insulin positive cells from donors with higher HbA1C [ 89 ]. Interestingly, while PPI treatment of patients with HbA1C ≤ 7% only resulted in an average of 0.05% decrease in HbA1C, patients with HbA1C > 7% and HbA1C > 9% showed 0.5% and 1.2% reduction in HbA1C, respectively [ 82 , 90 ]. Thus, further studies elucidating the mechanism in which PPI and gastrin improve glycemic control may help in directing this treatment approach to the appropriate patient population.…”
Section: Current Therapeutic Agentsmentioning
confidence: 99%
“…The observation shown in Figure 1 suggests that the age-dependent change in [Cl − ] s would have some physiological meanings. We categorized the age of persons taking medical examinations into six groups; (1) younger than 30 years old (<30), (2) equal to or older than 30 years old and younger than 40 years old (30s), (3) equal to or older than 40 years old and younger than 50 years old (40s), (4) equal to or older than 50 years old and younger than 60 years old (50s), (5) equal to or older than 60 years old and younger than 70 years old (shown as 60s), and (6) equal to or older than 70 years old (shown as 70 ). We considered a possibility that [Cl − ]s could be an index indicating metabolic condi tions in medical examinations based on the following reason.…”
Section: Age-dependent Changes In Venous Serum CLmentioning
confidence: 99%
“…However, even though O 2 consumption and CO 2 production are measured, certain momentary values of O 2 consumption and CO 2 production are not enough to estimate the metabolic condition of whole body, but continuous measurements of O 2 consumption and CO 2 production are required to detect the relatively chronic metabolic condition of whole body [1][2][3][4]. On the one hand, concentrations of electrolytes such as H + and HCO 3 − in the venous serum show the relatively chronic status of metabolic conditions [5][6][7][8][9], although acute changes in metabolic conditions would also affect H + and HCO 3 − concentrations in the venous serum with a time lag dependent on the degree and the time duration of the acute metabolic changes. Even though these measurements could provide crucial information on the metabolic status, these measurements require technically complicated processes.…”
Section: Introductionmentioning
confidence: 99%